Entrepreneurship and Female Leadership: A Systematic Literature Review from 2019 to 2023 - Osorio Pascacio, Patricia Sofía; Manrique Plácido, Juana Maribel; Yépez Pretel, Nidia Erlinda (LACCEI, 2024)
The present study aimed to describe quantitative metrics regarding publications on entrepreneurship and female leadership in Scopus, Google Scholar, Dialnet, and Alicia from 2019 to 2023. In this regard, the search was conducted by consulting the keywords "entrepreneurship" and "female leadership" in the mentioned databases. Subsequently, studies were filtered according to open access documents, publication years, and topic within the database itself, for subsequent literature review. At the end of the review, the last filter was applied based on exclusion criteria, resulting in a final outcome of 17 studies. It was evident that in 2021, there were 6 publications, representing the highest peak of scientific production. Additionally, it was noted that Peru had the highest number of studies published regarding entrepreneurship and female leadership. The most frequent keywords in studies on this topic were: female entrepreneurship, female leadership, women entrepreneurs, female empowerment. The results obtained demonstrate the limited production of research on the subject, particularly in Latin America, with only Peru having found studies. Therefore, there is a need to increase publications to provide a broader analysis and perspective on this topic. Furthermore, it is concluded that there is a scarcity of studies that relate both variables, whereas there are studies that show an analysis of each variable independently.